Cassava Chaff Ash as Potential Adsorbent for Arsenic Ions Removal from Aqueous Solution: Evaluations of Isotherms, Kinetics, and Thermodynamic Properties - Ali El-Rayyes; Arogundade Ibrahim; Ezekiel Folorunsho Sodiya; Edwin Andrew Ofudje; Akeem Adesina Bamgbade; Moamen S. Refat; Amnah Mohammed Alsuhaibani; James Asamu Akande (BioResources)
Cassava chaff in its raw and heat-treated (ash) forms was studied as an adsorbent for the removal of arsenic (As(V)) from aqueous solutions in a batch process. The findings indicated that pH significantly influenced As adsorption efficiency on raw cassava chaff, with optimal adsorption (78.6%) observed at a pH of approximately 4.5. Adsorption isotherm modeling revealed that the Langmuir model was more applicable to heat-treated cassava chaff, with maximum adsorption capacity of 101 mg/g, whereas the Freundlich model better described As adsorption on raw cassava chaff with maximum adsorption capacity of 82.2 mg/g. Kinetic studies showed that the pseudo-second-order model accurately represented As adsorption onto raw cassava chaff, while the pseudo-first-order model best fit the kinetics for heat-treated cassava chaff. The enthalpy change for heat-treated cassava chaff and raw sample were +35.3 kJ/mol and +55.3 kJ/mol, respectively, suggesting the process to be endothermic. Information from Fourier transform infrared analysis revealed that the adsorbent was made up of cellulose and hemicellulose materials. Functional groups including OH, C=C, C=O, and C-O may be involved in the uptake of As(V) ions. This work highlights heat-treated cassava chaff as a promising, robust solution for As-contaminated water treatment.